Saxagliptin affects long-bone microarchitecture and decreases the osteogenic potential of bone marrow stromal cells - Sbaraglini, María Laura (2014)
Diabetes mellitus is associated with a decrease in bone quality and an increase in fracture incidence. Additionally, treatment with anti-diabetic drugs can either adversely or positively affect bone metabolism. In this study we evaluated: the effect of a 3-week oral treatment with saxagliptin on femoral microarchitecture in young male non-type-2-diabetic Sprague Dawley rats; and the in vitro effect of saxagliptin and/or fetal bovine serum (FBS), insulin or insulin-like growth factor-1 (IGF1), on the proliferation, differentiation (Runx2 and PPAR-gamma expression, type-1 collagen production, osteocalcin expression, mineralization) and extracellular-regulated kinase (ERK) activation, in bone marrow stromal cells (MSC) obtained from control (untreated) rats and in MC3T3E1 osteoblast-like cells. In vivo, oral saxagliptin treatment induced a significant decrease in the femoral osteocytic and osteoblastic density of metaphyseal trabecular bone and in the average height of the proximal cartilage growth plate; and an increase in osteoclastic tartrate-resistant acid phosphatase (TRAP) activity of the primary spongiosa. In vitro, saxagliptin inhibited FBS-, insulin- and IGF1-induced ERK phosphorylation and cell proliferation, in both MSC and MC3T3E1 preosteoblasts. In the absence of growth factors, saxagliptin had no effect on ERK activation or cell proliferation. In both MSC and MC3T3E1 cells, saxagliptin in the presence of FBS inhibited Runx2 and osteocalcin expression, type-1 collagen production and mineralization, while increasing PPAR-gamma expression. In conclusion, orally administered saxagliptin induced alterations in long-bone microarchitecture that could be related to its in vitro down-regulation of the ERK signaling pathway for insulin and IGF1 in MSC, thus decreasing the osteogenic potential of these cells.